Student Survey on Creative Technology-Based Summary Tasks to Strengthen 21st-Century Teaching Skills - Royani, Shinta; Riska, Fati Matur; Parno (Universitas Negeri Semarang, 2025)
21st-century education demands that prospective educators possess creativity, critical thinking, communication, collaboration, and digital literacy. This study aims to determine students' responses to the implementation of the Creative Technology-Based Summary Task as a strategy for strengthening 21st-century teaching skills. The study used a survey method with a five-point Likert scale questionnaire instrument given to 20 students of the Physics Education Master's Program at the State University of Malang who had taken the Physics Learning Foundations course. Data were analyzed descriptively to obtain an overview of the tendencies of student responses. The results showed that the majority of students responded positively to the implementation of this task. 85% of respondents considered this task to strengthen critical thinking skills, 90% considered it to increase creativity, 75% considered it contributed to communication skills, and 80% stated that it was able to increase engagement and digital literacy. The variety of creative products produced by students included posters, comics, educational games, Instagram feeds, educational videos, and TikTok content. Reflecting students' ability to integrate technology into learning. This study concluded that the Creative Technology-Based Summary Task plays an important role in equipping students with 21st-century pedagogical competencies. It is recommended that further research involve a wider range of respondents, across study programs, and examine the long-term impact on teaching practices in schools.